Impact Assessment of Parthenium hysterophorus L Induced Changes in Biological Parameters of Mammals - Sovind Kumar; Sabita Verma (The Bioscan, 2025)
The present assessment study has been undertaken to review the toxic effects of exposure of one of the most important plant of Invasive Alien Plant Species (IAPS) group i.e. Parthenium hysterophorus. It endangers human health and livestock by disrupting the important glands function. The scientific studies have revealed that pollens, trichomes and other parts of Parthenium hysterophorus exhibit a wide spectrum of biological activities such as allergic, cytotoxic and phytotoxic. It contains certain chemical like sesquiterpene lactone, polyphenols and flavonoids which are harmful to human and other livestocks health. Our FTIR study of functional groups present in different parts of Parthenium plant has validated the presence of harmful toxic chemicals.Its toxic symptoms creates problem in the gastrointestinal tract, hametological parameters and degenerative changes in liver and kidneys. It has also been observed that P. hysterophorus can also disrupt endocrine function in mice. A valiant attempt has been made in this paper to consolidate and compile the research work carried out so far for the quick assessment of deleterious impact of Parthenium exposure on mice and rats on their respective reproductive and endocrine systems. This present work would pave the way for its vast pharmacologic applications for the development of a potential multipurpose medicinal agent.